2009
DOI: 10.3892/or_00000553
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 expression of micrometastasis-positive sentinel nodes in breast cancer patients

Abstract: Abstract. A number of methods have been established for identifying sentinel nodes (SNs). In the present study, we attempted to clarify the immunological status of SNs with or without micrometastasis in breast cancer patients. SNs were identified by the dye-and Á probe-guided method. Total RNA was extracted from the SNs, and the expression of T-BET, GATA-3, and FOXP3 were evaluated using quantitative realtime reverse transcriptase-polymerase chain reaction (RT-PCR). Micrometastasis was identified as microscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…These data indicate that Hsp27-differentiated MACs may have induced the preferential differentiation of naive T cells to IL-13-producing T cells (Th2) prior to tolerance induction. Although a Th1!Th2 shift, as reported in breast cancer (44,45), is not confirmed in our current experiments, they certainly indicate that Th1 cells are more affected than Th2 cells during a coculture of Hsp27 or M-CSF þ Hsp27-differentiated MACs with autologous T cells.…”
contrasting
confidence: 47%
“…These data indicate that Hsp27-differentiated MACs may have induced the preferential differentiation of naive T cells to IL-13-producing T cells (Th2) prior to tolerance induction. Although a Th1!Th2 shift, as reported in breast cancer (44,45), is not confirmed in our current experiments, they certainly indicate that Th1 cells are more affected than Th2 cells during a coculture of Hsp27 or M-CSF þ Hsp27-differentiated MACs with autologous T cells.…”
contrasting
confidence: 47%
“…It was indicated that FoxP3 + Tregs increased in the microenvironment of sentinel lymph nodes along with pathologically undetectable micrometastasis and were an independent prognostic predictor in patients with node-negative breast cancer [90]. In this context, it was observed that Treg response was induced at the micrometastasis level and persisted during metastasis progression in sentinel nodes in breast cancer patients [91].…”
Section: Possible Functions Of the T Cells In Disseminated Breast Cancermentioning
confidence: 95%
“…However, there have been contradictory reports about the expression and functions of FOXP3 in breast cancer cells. Matsuura et al 10 found that the FOXP3 mRNA and protein were highly expressed in tumour tissue from breast cancer patients, and that expression was closely associated with tumour recurrence and overall survival rate. We suggest that that FOXP3 could be a new prognostic factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Studies have found that some tumour cells expressing FOXP3 at a high level have immunosuppressive effects similar to those of Treg cells; through such an effect or other, unknown mechanisms, the immune killing of tumour cells (such as pancreatic cancer cells and breast cancer cells) may be directly or indirectly inhibited, resulting in escape from immune surveillance. [9][10][11] These findings have provided new directions for studying of the mechanism of tumour immune escape. However, there have been few studies on squamous cell carcinoma, especially of the head and neck.…”
Section: Introductionmentioning
confidence: 95%